Beyond a Single Damping Coefficient: Experimental Mapping of Nonlinear and Stroke-Dependent Automotive Shock-Absorber Behaviour - Avicenna An-Nizhami; Ignatius Gunawan Widodo; Muhammad Showi Nailul Ulum; Elfrida Rizky Riadini; Ahmad Mamba’udin; Yuris Bahadur Wirawan (Journal of Mechanical Engineering and Applied Technology, 2026)
Shock absorbers are commonly represented by a constant viscous damping coefficient, although their actual force response may vary nonlinearly with piston velocity, stroke amplitude, and operating conditions. This study experimentally compared the damping characteristics of original and aftermarket rear shock absorbers using a laboratory test rig with variable-speed and variable-stroke operation. Both specimens were tested at strokes of 60, 90, and 120 mm and excitation frequencies of 0.5–2.0 Hz, corresponding to peak piston velocities of 0.0942–0.7539 m/s. Maximum damping forces were measured using a force gauge, and the resulting force–velocity relationships were evaluated before and after modification of the test rig. Three-term sinusoidal functions were also fitted to the measured data using the MATLAB Curve Fitting Tool. Both shock absorbers exhibited nonlinear digressive behaviour, characterised by a rapid force increase at low-to-intermediate velocities followed by a stroke-dependent high-speed plateau. Matched-velocity comparisons showed that damping force varied with stroke even at approximately equal peak velocities, demonstrating that the response was not governed by piston velocity alone. Using the post-modification data, the aftermarket shock absorber generated an average damping force 15.8% higher than the original unit over the complete test matrix. Its peak force exceeded that of the original shock absorber by 29.4%, 9.8%, and 12.6% at strokes of 60, 90, and 120 mm, respectively. The corresponding apparent damping coefficients were also consistently higher for the aftermarket unit. These findings demonstrate that shock-absorber performance should be evaluated using experimentally determined force–velocity operating maps across multiple strokes and velocities rather than a single nominal damping coefficient.